The Effects of Competitive, Cooperative, and Individualistic Classroom Interaction Models on Learning Outcomes in Mathematics in Nigerian Senior Secondary Schools. (9th February 2012) - Oloyede, E. O.; Adebowale, O. F.; Ojo, A. A.
Abstract : The study sought to find out the relative effectiveness of three classroom interaction strategies which are known to affect students' learning outcomes in Mathematics. 484 senior secondary school three (SSSIII) students randomly selected through judgmental and stratified random sampling from government-owned secondary schools in Ikere and Ado-Ekiti local government areas of Ekiti state participated in the study. The instrument was a self-constructed one, validated and used for collecting data and titled "Mathematics Achievement Test (MAT)." The experimental treatment lasted for four weeks, and the data collected were analyzed using one-way ANOVA, ANCOVA, two-way ANCOVA, and Tukey HSD post hoc pairwise comparisons analysis. The findings showed that the students' learning outcomes in Mathematics were better promoted by the cooperative and competitive strategies but rather minimally by both individualistic and conventional strategies.